2020
DOI: 10.14814/phy2.14437
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous sensory nerve‐mediated microvascular vasodilation in normotensive and prehypertensive non‐Hispanic Blacks and Whites

Abstract: Relative to non-Hispanic Whites, non-Hispanic Blacks are disproportionately affected by elevated blood pressure (BP). It is unknown whether race or subclinical increases in BP affect the ability of cutaneous sensory nerves to induce cutaneous microvascular vasodilation. Sixteen participants who self-identified as non-Hispanic Black (n = 8) or non-Hispanic White (n = 8) were subgrouped as normotensive or prehypertensive. Participants were instrumented with three intradermal microdialysis fibers: (a) control, (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 77 publications
(139 reference statements)
1
15
0
Order By: Relevance
“…Type 2 diabetes and chemotherapy are widely known to be risk factors for developing sensory nerve dysfunction (i.e., diabetic sensory neuropathy and chemotherapy-induced neuropathy, respectively), but some evidence suggests race and blood pressure may also be risk factors for developing sensory nerve dysfunction (11,17,21,51). Additionally, we recently observed that the temperature threshold for cutaneous sensory nerve activation is shifted to a higher temperature in non-Hispanic blacks; however, we were unable to assess the magnitude of sensory nerve-mediated vasodilation in our previous study (52). A recent study by Patik et al (45) found that the magnitude of the initial peak response was reduced in non-Hispanic blacks relative to non-Hispanic whites; however, determination of the contribution of sensory nerves to the initial peak was not assessed in that particular study.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Type 2 diabetes and chemotherapy are widely known to be risk factors for developing sensory nerve dysfunction (i.e., diabetic sensory neuropathy and chemotherapy-induced neuropathy, respectively), but some evidence suggests race and blood pressure may also be risk factors for developing sensory nerve dysfunction (11,17,21,51). Additionally, we recently observed that the temperature threshold for cutaneous sensory nerve activation is shifted to a higher temperature in non-Hispanic blacks; however, we were unable to assess the magnitude of sensory nerve-mediated vasodilation in our previous study (52). A recent study by Patik et al (45) found that the magnitude of the initial peak response was reduced in non-Hispanic blacks relative to non-Hispanic whites; however, determination of the contribution of sensory nerves to the initial peak was not assessed in that particular study.…”
Section: Discussionmentioning
confidence: 71%
“…Whether race and/or blood pressure status adversely affect sen-sory nerve function is not completely known; however, some evidence suggests overt hypertension and race may be risk factors for the development of sensory neuropathy (11,17,21). Our laboratory recently demonstrated that the temperature threshold eliciting cutaneous sensory nerve activation is shifted to a higher temperature in non-Hispanic blacks relative to non-Hispanic whites, and this rightward shift is largely due to a reduction in bioavailable NO (52). In this previous study we used a slow, ramp local heating protocol and were unable to determine the magnitude of sensory nerve-mediated vasodilation (27,52).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The pathophysiology of sensory neuropathy is linked to microvascular and endothelial dysfunction (Cameron et al., 2001) and we originally hypothesized that this dilatation would be attenuated in our patient group. Indeed, prehypertensive adults and non‐hypertensive black men and women have an attenuated cutaneous sensory nerve‐mediated vasodilatation response, reflective of and accompanied by reductions in endothelium‐dependent NO‐mediated dilatation (Patik et al., 2018; Turner et al., 2020; Wong et al., 2020). In these studies, as with ours, local heating applied to the skin was used to activate the sensory nerve‐mediated increase in skin blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of sensory neuropathy is linked to microvascular and endothelial dysfunction (Cameron et al., 2001) and sensory nerve dysfunction exacerbates vascular dysfunction in rodent models of hypertension (Watson et al., 2002). Indeed, overt hypertension may be an independent risk factor for sensory neuropathy in humans (Cohen et al., 1998; Hebert et al., 2017), and prehypertensive adults have an attenuated cutaneous sensory nerve‐mediated vasodilatation response, reflective of and accompanied by reductions in endothelium‐dependent NO‐mediated dilatation (Turner et al., 2020; Wong et al., 2020). Together, these data suggest that sensory nerve‐mediated microvascular dilatation may be attenuated in populations with attenuated NO bioavailability, and that this attenuation may contribute to the development of CVD.…”
Section: Introductionmentioning
confidence: 99%